A Portrait of Self-Regulation of Students Who Trial in Junior High School - Bathari Sanggar Kirana; Nurfarhanah; Azmatul Khairiah; Triave Nuzila Zahri (Global Action and Education for Society, 2025)
This research is motivated by the discovery that many students currently have low self-regulation, this is caused by various factors, one of which is deviant behavior that is currently rampant among students, namely truancy. This study aims to describe students' self-regulated aspects in terms of: 1) overall aspects, 2) planning aspects (forethought), 3) work skills aspects (performance control), 4) self-reflection aspects. The research method used is a quantitative method with a descriptive approach. The sample in this study was 100 students who had been truant at SMP Muhammadiyah 6 Padang who were selected using a purposive sampling technique. The data obtained by giving a research questionnaire in the formof a self-regulation instrument to students. Then the data were collected and analyzed using descriptive statistical analysis techniques. The results of the study showed that: 1) self-regulation of truant students in general is in the high category, 2) self-regulation of truant students based on the planning aspect (forethought) is in the high category, 3) self-regulation of truant students based on the work skills aspect (performance control) is in the high category, 4) self-regulation of truant students based on the selfreflection aspect is in the high category. Based on the research results obtained, BK teachers at schools can provide various assistance by providing BK services such as: individual counseling, group guidance services, information services and group counseling services to maintain and improve self-regulation in students.